POLITIK IDENTITAS MELAYU MALAYSIA DAN MULTIKULTURALISME PADA FILM UPIN & IPIN : Politik Identitas dan Multikulturalisme di Film Upin Ipin - wahyudi. S, fazril wahyudi.s; Widia Ierdiana; Siti Badariah; Rindi Wulansari; Nadilla; Fitri Nurzana; Novrianti; Aditya Padini Syah (STISIP Widyapuri Mandiri Sukabumi, 2024)
This research aims to see how Malaysian Malay identity politics and multiculturalism appear in the film